ALAT BATU SITUS SEMEDO: KERAGAMAN TIPOLOGI DAN DISTRIBUSI SPASIALNYA - Sofwan Noerwidi; Siswanto (Berkala Arkeologi, 2014)
Semedo site produces a huge number of stone artifacts. Until now, there are already find more than 500 pieces of stone artifact which majority use chert and silicified limestone as raw materials. This paper will discuses about typology diversity based on technological aspect and spatial distribution of its localities. Diversity aspect which discussed including; typo-technology, raw material, dimension, and its relation with lateral distribution in Semedo site. Genaraly, those artifacts could identified as two group, which are; massif and non-massif artifacts. Some localities which produce much number of stone artifacts are Rengas, Jurugan, Julang, and Kalen Kawi. Based on this analysis, the result took Semedo site on important position as part of Pleistocene sites which correlated with migration-colonisation of early human in Java.